Metal Forming Process, Tools, Design - Kazeminezhad, Mohsen (IntechOpen, 2012)
Different aspects of metal forming, consisting of process, tools and design, are presented in this book. The chapters of this book include the state of art and analysis of the processes considering the materials characteristics. The processes of hydroforming, forging and forming of sandwich sheet are discussed. Also, a chapter on topography of tools, and another chapter on machine tools are presented. Design of a programmable metal forming press and methods for predicting forming limits of sheet metal are described.